Dynamic nuclear polarization enhanced solid-state NMR studies of surface modification of gamma-alumina - Mais, Marco; Paul, Subhradip; Barrow, Nathan S.; Titman, Jeremy J. (Johnson Matthey PLC, 2018)
Dynamic nuclear polarization (DNP) gives large (>100-fold) signal enhancements in solid-state NMR spectra via the transfer of spin polarization from unpaired electrons from radicals implanted in the sample. This means that the detailed information about local molecular environment available for bulk samples from solid-state NMR spectroscopy can now be obtained for dilute species, such as sites on the surfaces of catalysts and catalyst supports. In this paper we describe a DNP-enhanced solid-state NMR study of the widely used catalyst gamma-alumina which is often modified at the surface by the incorporation of alkaline earth oxides in order to control the availability of catalytically active penta-coordinate surface Al sites. DNP-enhanced 27Al solid-state NMR allows surface sites in gamma-alumina to be observed and their 27Al NMR parameters measured. In addition changes in the availability of different surface sites can be detected after incorporation of BaO.